Method Of Teaching Reading Applied In SMPN 1 Sidoharjo At TheEighth Grade In 2012/2013 Academic Year - Ibrahima, Sabrina Restu; , Drs. Djoko Srijono, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
This research aims to describe method used by teacher in teaching reading applied in SMP N 1 Sidoharjo at the eighth year in 2012/2013 academic year, problem faced by the teacher, and the ways to overcome the problems. This research is a descriptive research. The writer collets the data by observing teaching-learning process and conducting interview. The data include: event, informant, and field note. The methods of collecting data are observation, interview, and analyzing document. The techniques for analyzing data are; (1) the writer presents the detail description of the method of teaching reading in SMP N 1 Sidoharjo, (2) the writer presents the detail description of the problems faced by teacher in teaching reading in SMP N 1 Sidoharjo, (3) the writer presents the detail description of how the teacher overcome the problems, (4) the writer presents conclusion and then give suggestion based on data analysis. The result of the research are; (1) the method applied by the teacher in teaching reading to the eighth grade in SMP N 1 Sidoharjo is KWL method, K (what the student Know), W (what the student Want to know), L (what the student Learn), (2) the problems faced by the teacher in teaching reading at the eighth grade in SMP N 1 Sidoharjo are students lack of vocabulary mastery and the teacher has limited time, (3) the ways to overcome the problems are: performing drama, role playing and playing the puzzle, giving additional task or homework to students.